2014
DOI: 10.1088/1748-6041/9/2/025013
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial properties and biocompatibility of a Ti–Cu sintered alloy for biomedical application

Abstract: The antibacterial activity, the cytotoxicity and the cell function of a sintered Ti-10 wt% Cu alloy were investigated in order to assess the suitability of the alloy for biomedical application. The antibacterial activity of the alloy was investigated by a plate-count method and the cytotoxicity was studied by examining the MG63 cell response by CCK8 assessment. The cell function was monitored by measuring the AKP activity. The Cu ion released from the Ti-Cu alloy was also measured by an inductively coupled pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…On the other hand, Hong et al [13] revealed that adding a proper amount of Cu gave SUS 304 stainless steel an excellent antibacterial property. Some other studies [14,15] also confirmed the good antibacterial properties of Ti-Cu fabricated by powder metallurgy. Compared with antibacterial coatings, alloying with Cu or Ag additives in metals could release antibacterial ions over a longer period.…”
Section: Introductionmentioning
confidence: 60%
“…On the other hand, Hong et al [13] revealed that adding a proper amount of Cu gave SUS 304 stainless steel an excellent antibacterial property. Some other studies [14,15] also confirmed the good antibacterial properties of Ti-Cu fabricated by powder metallurgy. Compared with antibacterial coatings, alloying with Cu or Ag additives in metals could release antibacterial ions over a longer period.…”
Section: Introductionmentioning
confidence: 60%
“…This suggests that alloying elements Sn in Ti-based alloys is biocompatible for surgical implants. Another, Liu et al studied the antibacterial activity, cytotoxicity and cell function in the sintered Ti-10 wt.% Cu alloy [40]. The Cu ion release was thought to contribute to the strong antibacterial property, but the Cu ion did not cause cell cytotoxicity, showing good cell cytocompatibility.…”
Section: Eismentioning
confidence: 99%
“…Another, the 2.5 wt% Cu addition to Ti6AlxV(x = 1.5 and 4) has been already commercially used to nano-Ti 2 Cu precipitates 24 . Another, Liu et al 25 reported that the antibacterial rates of the Ti-Cu alloy against E. coli and S. aureus after 7 h of incubation are 99.01% and 91.66%, respectively, indicating that the copper ions release from the Ti-Cu alloy and contribute to the strong antibacterial property, but the Cu ion did not lead to cell cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%